Alexander von Humboldt’s Poetry of Nature: Freedom and the Latin American Landscape - Millán, Elizabeth (Meridional. Revista Chilena de Estudios Latinoamericanos, 2014)
In this article, I present the Naturgemälde that Alexander von Humboldt created during his voyage from 1799-1804 to the equinoctial region of the earth. I suggest that Humboldt’s approach to nature balanced empirical mastery with aesthetic appreciation, a balancing that opened a new space of freedom for the people and places of Latin America. Humboldt helped to liberate the Latin American landscape from the dominant Eurocentric views of its anti-American detractors. I argue that this valuable balancing of mastery and freedom is rooted in some of the philosophical insights of the early German Romantics. Further, by way of reference to the work of Theodor Adorno, Martin Seel, and César Aira, I demonstrate the enduring relevance of Humboldt’s approach to landscape.